Agricultural land market in Slovakia - S. Buday (Agricultural Economics (AGRICECON), 2007)
The agricultural land market in Slovakia has noted an increased dynamics recently. Such situation was a result of entering big foreign investors, particularly car factories, which had bought agricultural land for construction purposes. It resulted in the raised prices of plots. Agricultural land prices sold for the further agricultural use are markedly lower from the national point of view than in the EU-15. Such prices are also the third lowest ones within the new member countries of the EU.